2016
DOI: 10.1016/j.jmacro.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Trade partner diversification and growth: How trade links matter

Abstract: We analyze the effects of a country's export connections on its income growth using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…For pharmaceutical firms, developing related products contributes to long-term firm performance as well as short-term firm performance. In general, a firm's diversification strategy is recommended within its manageable capacity because once the firm extensively focuses its diversification on related products, it may lose out on exploring new opportunities (Önder & Yilmazkuday, 2016;Palich et al, 2000;Pierce & Aguinis, 2013). For pharmaceutical firms, however, we found that RPD is beneficial even in the long term.…”
Section: Discussionmentioning
confidence: 81%
“…For pharmaceutical firms, developing related products contributes to long-term firm performance as well as short-term firm performance. In general, a firm's diversification strategy is recommended within its manageable capacity because once the firm extensively focuses its diversification on related products, it may lose out on exploring new opportunities (Önder & Yilmazkuday, 2016;Palich et al, 2000;Pierce & Aguinis, 2013). For pharmaceutical firms, however, we found that RPD is beneficial even in the long term.…”
Section: Discussionmentioning
confidence: 81%
“…In this vein, ED is documented with several impacts (Le et al, 2020;Osakwe et al, 2018). For instance, Önder and Yilmazkuday (2016) argue that diversification in trading partners has a positive impact on economic growth. Egger and Etzel (2012) add that trade openness with a fully symmetric partner country could induce higher employment and welfare.…”
Section: Export Diversification and Economic Fluctuationsmentioning
confidence: 99%
“…Were (2015) used the panel data technique to investigate the effect of trade on economic growth and investment in least developed economies, while Eberhard-Ruiz and Moradi (2019) used satellite imagery of lights emanating from the Earth at night. These estimation techniques employed by different scholars can be broadly classified into the threshold model (Onder and Yilmazkuday, 2016), linear regression (Ghoshal, 2015), satellite imagery of lights emanating from earth at night (Eberhard-Ruiz and Moradi, 2019) and panel technique (Zahonogo, 2016;Kim et al, 2016).…”
Section: Review Of Related Literature 21 Theoretical Reviewmentioning
confidence: 99%